Implementation Plan in Response to the Board-Endorsed Recommendations for the IEO Report 'Behind the Scenes with Data at the IMF : An IEO Evaluation'. (Policy Papers; Policy Paper ;, 2016)
This paper sets out Management's response to the Independent Evaluation Office's (IEO) report entitled Behind the Scenes with Data at the IMF: An IEO Evaluation. The implementation plan proposes specific actions to address the recommendations of the IEO that were endorsed by the Board in its March 17, 2016 discussion of the IEO's report, namely: (i) develop a long-term strategy for data and statistics at the Fund; (ii) define and prioritize the Fund's data needs and support data provision by member countries accordingly; (iii) reconsider the role and mandate of the Statistics Department; (iv) reexamine the staff's structure of incentives in the area of data management; (v) make clear the limits of IMF responsibility regarding the quality of disseminated data, and clarify the distinction between 'IMF data' and 'official data.' The implementation of some of these proposed actions is already underway. The paper also explains how implementation will be monitored.